Blush in Lung Contusions Is Not Rare and Has a High Risk of Mortality in Patients With Blunt Chest Trauma - Tominaga, Naoki; Hayakawa, Mineji; Yokobori, Shoji (Frontiers in Medicine, 2022)
Background Patients with blunt chest trauma have a high mortality rate. The assessment of blush in hepatic and splenic trauma is important for determining the need for emergency hemostatic interventions. However, the frequency and importance of blush in lung contusions are unknown. Therefore, this study aimed to evaluate the frequency of blush in patients with lung contusions and elucidate the relationship between blush and the clinical outcomes of patients with blunt chest trauma. Materials and Methods In this retrospective observational study, we enrolled patients with an injury severity score of 16 or higher and a chest abbreviated injury scale (AIS) score of 3 or higher who were admitted to the emergency department of Hokkaido University Hospital from January 1, 2003, to December 31, 2016. Blush was defined as active extravasation of an intravascular contrast agent recognized on contrast-enhanced computed tomography. The date of trauma, trauma severity, treatments, and outcomes were obtained from the patients’ electronic medical records. Results During the study period, 83 patients had severe lung contusions and 13 had blush. In-hospital mortality of patients with blush was significantly higher than that of patients without blush (53 vs. 10%, P < 0.001). Patients with blush required thoracic drainage more frequently (100 vs. 71%, P < 0.001) and support through mechanical ventilation more often (100 vs. 64%, P < 0.001) and for a longer duration (median duration, 0 vs. 25 days, P = 0.001) than patients without blush. Conclusions Our study revealed that blush in lung contusions was not rare and was associated with a high risk of mortality in patients with severe blunt chest trauma. Clinicians should not hesitate to intervene if blush is detected in a lung contusion of a patient with blunt chest trauma.